1995
DOI: 10.1016/0735-1097(94)00519-v
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognosis of patients with anginalike chest pain and normal coronary angiographic findings

Abstract: Patients with typical angina or anginalike chest pain and normal coronary angiograms have a good long-term prognosis despite persistence of pain for many years; coronary morbidity and mortality are similar to those of the overall population. An increased risk for the development of coronary events is present mainly in patients with elevated risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
1
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(97 citation statements)
references
References 33 publications
6
81
1
9
Order By: Relevance
“…Most studies investigating the relationship between NCCP and cardiac morbidity and mortality, are conducted with NCCP patients with negative coronary angiography. These studies have reported an excellent mortality prognosis with survival rates of 91-98% up to 12 years after the angiographic assessments (17)(18)(19). In contrast, two population-based studies reported that the mortality rate of chest pain patients is higher than that of the normal population.…”
Section: Prognosis Of Chest Pain Patientsmentioning
confidence: 87%
“…Most studies investigating the relationship between NCCP and cardiac morbidity and mortality, are conducted with NCCP patients with negative coronary angiography. These studies have reported an excellent mortality prognosis with survival rates of 91-98% up to 12 years after the angiographic assessments (17)(18)(19). In contrast, two population-based studies reported that the mortality rate of chest pain patients is higher than that of the normal population.…”
Section: Prognosis Of Chest Pain Patientsmentioning
confidence: 87%
“…Studies supporting good cardiovascular outcome included young adults who had less cardiac risk factors. 56 Lichtlen et al 60 reported that NCCP patients experiencing a coronary event had significantly more risk factors like hypercholesterolemia, hypertension, smoking, and diabetes mellitus than those without a coronary event. One possible conclusion could be that age ≥55 years with increased cardiac risk factors could confer a long-term cardiovascular risk compared with NCCP patients between 45 and 50 years of age with less risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the prognosis of syndrome X and microvascular angina, there have been some reports showing favorable prognoses in patients with angina-like chest pain and normal coronary arteriograms; [11][12][13][14][15][16][17][18][19][20] However, progressive reduction in left ventricular function has also been described in other reports from Western countries, 9,10 but to date there have been few reports on the prognosis of syndrome X in Japanese patients. 20 This study describes the clinical features and long-term prognosis of patients with microvascular angina, diagnosed by our strict criteria, who underwent cardiac catheterization and endomyocardial biopsy from 1988 to 1997 at Showa University Hospital.…”
mentioning
confidence: 99%